EARLY DETECTION OF BREAST CANCER USING ULTRA WIDE BAND SLOT ANTENNA - Yusnita Rahayu; Immanuel Waruwu (Universitas Mercu Buana, 2019)
Breast cancer is the transformation of normal cells in the breast area into a malignant tumor, which is the second largest disease as a cause of death for women. Early detection is one way to avoid significant risks in breast cancer. X-ray mammography and magnetic resonance imaging (MRI) techniques are used to detect breast cancer. However, those techniques have several limitations. Ultra-wideband (UWB) microwave imaging, approved by The Federal Communications Commission (FCC) in the United States, has promising capabilities in detecting breast cancer. Microwave imaging uses a microstrip antenna that has the advantage of convenience, potentially low cost, and is a non-ionized and safe alternative. In this paper, the ultra-wideband microstrip antenna for breast cancer detection is proposed. The antenna was designed by adding some rectangular slots on a rectangular patch to meet the UWB specifications. The antenna works well at 8.41 GHz to 10.29 GHz with directivity of 6.451 dBi and SAR value of 1.6 W / kg. The antenna was simulated with breast phantom. The tumor sizes of 6 mm and 10 mm are added to evaluate the E/H fields and current density with and without tumor. The highest E-Field value of 928.8 V / m was obtained at 10 GHz with a 10 mm tumor size. The highest H-Field value of 4.06 V / m was achieved at 10 GHz with a 6 mm tumor size. From the simulation, the E/H-field and current density are higher if there is a tumor in the breast compared to the breast without the tumor.